2005
DOI: 10.1002/mrd.20386
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis increases SUMO-1 protein expression and conjugation in mouse periovulatory granulosa cells in vitro

Abstract: The small ubiquitin-related modifier-1 (SUMO-1) with broad cellular expression has been implicated in a range of cellular processes, such as cell proliferation, differentiation, and apoptosis. As shown recently, SUMO-1 is expressed and regulated by gonadotropins, in particular an ovulatory hCG stimulus in mouse granulosa cells in vivo. To test the hypothesis that modulation of granulosa cell apoptosis changes SUMO-1 expression during granulosa cell differentiation in the mouse ovary, we demonstrate that proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…In previous studies, P 4 inhibited apoptosis in rat endometrial epithelial cells, which expressed functional nuclear PR in vitro (51), whereas RU-486 induced apoptosis in rabbit uterine epithelium in vivo (57). Our laboratory has also demonstrated that PR antagonists induce apoptosis in mouse ovarian granulosa cells that were expressing nuclear PR in vivo (62) and in vitro (63). These demonstrations suggest that the suppression of apoptosis is likely mediated by existence of nuclear PR in P 4 target tissues.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies, P 4 inhibited apoptosis in rat endometrial epithelial cells, which expressed functional nuclear PR in vitro (51), whereas RU-486 induced apoptosis in rabbit uterine epithelium in vivo (57). Our laboratory has also demonstrated that PR antagonists induce apoptosis in mouse ovarian granulosa cells that were expressing nuclear PR in vivo (62) and in vitro (63). These demonstrations suggest that the suppression of apoptosis is likely mediated by existence of nuclear PR in P 4 target tissues.…”
Section: Discussionmentioning
confidence: 67%
“…Recently Shao et al [13], [14] reported that Sumo-1, based on immunohistochemical analyses, is expressed in both healthy and atretic mouse granulosa cells in vivo , suggesting that Sumo-1 may function both during follicular development and atresia. We performed western blotting on protein extracts and immunofluorescence on sections of 4-week mouse ovaries, using specific antibodies for Foxl2, Pias1, Ubc9 and Sumo-1.…”
Section: Resultsmentioning
confidence: 99%
“…SUMO-1 protein is widely expressed in various tissues, and in particular it has already been reported in the entire granulosa cell population of all follicles, from primordial to early antral stage, in ovaries of immature mice [14]. Stimulation of LH receptors in granulosa cells results in down-regulation of SUMO-1 expression with concomitant induction of ovulation [14]. SUMO-1 has also been localized in male germ cells and somatic cells of mouse and rat testes [19] as well as in human male germ and somatic cells [20].…”
Section: Discussionmentioning
confidence: 98%
“…A variety of stress conditions, including elevated temperature, ethanol or H 2 O 2 exposure, and hypertonic conditions have been shown to cause changes in the sumoylation pattern for both vertebrates [41,46], yeast [32], and plant [45] cells. In addition to changes in response to stressors, significant changes in overall sumoylation patterns have also been observed for normal differentiating cells [42,47], during induction of apoptosis [48], and for cancerous cells [28]. These combined results suggest the sumoylation contributes to multiple cellular processes that are activated by changes in cellular environment.…”
Section: Conditional Sumoylationmentioning
confidence: 88%